2011
DOI: 10.1016/j.jmb.2010.12.042
|View full text |Cite
|
Sign up to set email alerts
|

Structures of the Class D Carbapenemase OXA-24 from Acinetobacter baumannii in Complex with Doripenem

Abstract: The emergence of class D β-lactamases with carbapenemase activity presents an enormous challenge to health practitioners, particularly with regard to the treatment of infections caused by Gram negative pathogens such as Acinetobacter baumanii. Unfortunately, class D β-lactamases with carbapenemase activity are resistant to β-lactamase inhibitors. To better understand the details of the how these enzymes bind and hydrolyze carbapenems, we have determined the structures of two deacylation-deficient variants (K84… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
166
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 68 publications
(178 citation statements)
references
References 42 publications
12
166
0
Order By: Relevance
“…Furthermore, the hydroxyethyl hydroxy group can adopt an orientation suitable for nucleophilic attack onto the ester carbonyl (i.e., the Bürgi–Dunitz trajectory),14 with the carbamylated lysine apparently positioned to act as a general base 12, 13. Although this conformation of the hydroxyethyl side chain was not observed in related crystal structures (Figure S27), these structures depict enzymes in which the lysine is not carbamylated (e.g., due to low pH or mutations) 5, 15, 16…”
mentioning
confidence: 85%
“…Furthermore, the hydroxyethyl hydroxy group can adopt an orientation suitable for nucleophilic attack onto the ester carbonyl (i.e., the Bürgi–Dunitz trajectory),14 with the carbamylated lysine apparently positioned to act as a general base 12, 13. Although this conformation of the hydroxyethyl side chain was not observed in related crystal structures (Figure S27), these structures depict enzymes in which the lysine is not carbamylated (e.g., due to low pH or mutations) 5, 15, 16…”
mentioning
confidence: 85%
“…Among the carbapenems, OXA-23 has a much higher turnover rate for imipenem than for meropenem, ertapenem, or doripenem (36). Despite the relatively low turnover rates for carbapenems displayed by these enzymes, it appears that they counter this through the presence of a "hydrophobic bridge" across the top of the active site, formed by phenylalanine 110 and methionine 221 (35), as the presence of a corresponding bridge in OXA-40 has been shown to be responsible for tight binding of the carbapenems (38,39). Recently, it was demonstrated that OXA-146 has an expanded hydrolytic spectrum that includes ceftazidime, which is not hydrolyzed by the other class D OXA-type carbapenemases, while retaining its activity against the carbapenems (35).…”
Section: Oxa-23-like ␤-Lactamasesmentioning
confidence: 99%
“…The main acquired and most widely spread carbapenemases in A. baumannii are OXA-23, OXA-24, and OXA-58, which represent three different CHDL groups and are encoded as either chromosomal or plasmid-borne genes (8,14). Of these three group representatives, only the structure of OXA-24 has been elucidated (15)(16)(17). Structural analysis and mutagenesis studies of OXA-24 suggest that a hydrophobic cleft over the active site could be responsible for the widened substrate specificity of these enzymes; imipenem is hydrolyzed about 10-fold more efficiently than oxacillin (15).…”
mentioning
confidence: 99%